Dominant Health Discourses in Action: Constructing People with Disabilities as the "Inadmissible Other" in Canadian Immigration - El-Lahib, Yahya (Disability Studies Quarterly, 2016)
This paper reports on a Critical Discourse Analysis study situated within a postcolonial theoretical framework and informed by Foucauldian analysis and the lens of governmentality. The study examined official Canadian immigration documents and guidelines. Findings suggest that discourses of risk and protection are used to mask dominant health discourses that construct immigration applicants with disabilities as the "inadmissible Other". Implications for social work and other helping professions involved in facilitating immigration and settlement for newcomers with disabilities are discussed, and suggestions for future directions in research are offered.